Optimizing urinary tract infection diagnosis: time and resource efficiency with the Sysmex UF-4000i - Babacar Ndiaye; Moustapha Faye; Abdou Diop; Mareme Thiam; Rena Derwiche; Samba Diao; Thierno Abdoulaye Diallo; Chantal Mahou; Abdoulaye Seck (Microbiologia Medica)
Background: Urinary Tract Infections (UTIs) are common bacterial infections, primarily caused by Gram-negative bacteria, such as Escherichia coli. They affect approximately 150 million individuals worldwide annually, leading to high healthcare costs and significant morbidity. The standard diagnostic method, urine culture, has a turnaround time of 48-72 hours, often necessitating empirical antibiotic treatment, which may contribute to antibiotic resistance. Rapid, accurate diagnostic tools are essential to improve clinical microbiology practices.